Combustion Parameters of Spark Ignition Engine using Waste Potato Bioethanol and Gasoline Blended Fuels - B., Ghobadian; G., Najafi; R., Mamat; M., Abbasian (IOP Publishing, 2015)
The purpose of this study is to investigate the combustion parameters of a SI engine operating on bioethanol-gasoline blends. The combustion parameters from the engine running on bioethanol (derived from potato waste) and blended with gasoline (E5, E,10, El5 and 820) were evaluated and compared with gasoline fuel. A reactor was designed,fabricated and evaluated for bioethanol production from potato wastes. The results showed that increasing the bioethanol content in the blend fuel will desrease the heating value of the blended fuel and increase the octane number. Combustion parameters were evaluated and analyzed at different engine speeds and loads (1000-5000 rpm). Comparative studies of combustion development of bioethanol-gasoline blends at different concentrations have been carried out by analysis of pressure cycles in combustion chamber. The results revealed that increasing bioethanol concentration in blended fuels increases the cylinder pressure and its 1$ and 2"d derivatives (P(0), P'(0) and P"(e)) compared to the neat gasoline fuel. The sthanol fuel has a higher volumetric efficiency than gasoline. At the constant engine speed, the cylinder pressure are increased with the improvement of volumetric efficiency. Moreover, using bioethanolgasoline blends will increase the heat release (Q.(0)) and worked of the cycle. This improvement was due to the high oxygen percentage in the ethanol. This better combustion parameters and effrciency suggests that using ethanol as fuel can prevent the pre-mature combustion, and thus improve the anti-knock characteristics